Quantum Geometric Engineering of Dual Hall Effects in 2D Antiferromagnetic Bilayers via Interlayer Magnetic Coupling - Zhenning Sun; Tao Wang; Hao Jin; Xinru Li; Yadong Wei; Jian Wang (Advanced Science)
Abstract The interplay between quantum geometry and magnetic order offers a novel strategy for designing next‐generation nanodevices. Here, it is demonstrated that interlayer magnetic coupling in two‐dimensional (2D) CoPSe3 bilayers enables precise control over quantum geometric mechanisms, unlocking dual intrinsic Hall effects. The first‐principles calculations reveal that the altermagnetic (AM) phase exhibits a giant anisotropic anomalous Hall effect (AHE) (σxy ≈46 S cm−1) driven by Berry curvature localized at generic k‐points, while the PT‐symmetric antiferromagnetic (AFM) phase hosts an intrinsic second‐order nonlinear anomalous Hall effect (NAHE) (χxyy ≈ 160 µS V−1) originating from quantum metric accumulation at high‐symmetry k‐points. By tuning interlayer magnetic couplings, reversible switching between these phases is achieved, leveraging their distinct band structures and symmetry constraints. The Néel‐vector‐dependent AHE in the AM phase and the symmetry‐protected NAHE in the AFM phase highlight quantum geometry as a versatile tool for manipulating transport properties. This work establishes 2D antiferromagnets as a promising platform for multifunctional device architectures, bridging linear and nonlinear magnetoelectric responses through tailored quantum geometric engineering.